Degradation of elephant grass silages with annatto by-product - Do Rêgo, Aníbal Coutinho [UNESP]; Duarte Cândido, Magno José; Pereira, Elzania Sales; Feitosa, José Valmir; Teles Rêgo, Margareth Maria (FapUNIFESP (SciELO), 2010)
To evaluate the dry matter, neutral detergent fiber and crude protein in situ degradation of elephant grass silages with five levels (0; 4; 8; 12 and 16%, on a fresh matter basis) of annatto grain by-product (AGBP), this work was carried out. A split-plot design, consisting on the addition levels the plots and the incubation times the sub-plots, with four replicates, was adopted. For the silages making, the elephant grass was cut 70 days-old and mixed to the by-product, in 20 plastic drums. The samples were dried, grid in a bolter of 5 mm mesh, being used 3 g of samples in each nylon bag, for incubation in the rumem for 0; 6; 48 e 96 hours; 2 ram without defined breed were used. Was observed increased the disappearance of the DM until the level 13.37% of addition of (AGBP) the elephant grass silages for the incubation time 48 hours, this level was that presented the most disappearance DM. For the NDF the disappearance increased until 16% of addition. For the whole of parameters of degradation, was observed that the level of addition of 16% of (AGBP) presented the most values for the potential and effective degradability of variables in question. The inclusion of the annatto grain by-product for elephant grass silage results in greater potential and effective degradability.
Degradação de silagens de capim-elefante contendo subproduto do urucum
Keywords: Bixa orellana L.; Degradability; Ensiling; Pennisetum purpureum schum; Sheep